2015
DOI: 10.1016/j.fob.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A novel link between FMR gene and the JNK pathway provides clues to possible role in malignant pleural mesothelioma

Abstract: HighlightsThe FMR gene is up-regulated in malignant pleural mesothelioma.Overexpression of dFMR causes overexpression of matrix metalloprotease.Overexpression of dFMR induces basement membrane degradation.Overexpression of dFMR results in upregulation of the JNK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
2
0
2
Order By: Relevance
“…The FMRP mRNA target-transcriptome was characterized in neurons [ 9 12 ], and an IPA analysis of FMRP-regulated mRNAs has shown that these targets are mainly involved in cytoskeleton remodeling and cell-to-cell signaling and interaction [ 6 ], mechanisms also involved in cancer progression. Indeed, it was recently shown that FMRP is also involved in progression of breast cancer [ 13 ], astrocytoma [ 14 ], malignant pleural mesothelioma [ 15 ], melanoma [ 16 ], and colon cancer [ 17 ]. Of note, in melanoma cells we identified the FMRP-regulated transcriptome that further confirmed its implication in the invasion of the tumor [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FMRP mRNA target-transcriptome was characterized in neurons [ 9 12 ], and an IPA analysis of FMRP-regulated mRNAs has shown that these targets are mainly involved in cytoskeleton remodeling and cell-to-cell signaling and interaction [ 6 ], mechanisms also involved in cancer progression. Indeed, it was recently shown that FMRP is also involved in progression of breast cancer [ 13 ], astrocytoma [ 14 ], malignant pleural mesothelioma [ 15 ], melanoma [ 16 ], and colon cancer [ 17 ]. Of note, in melanoma cells we identified the FMRP-regulated transcriptome that further confirmed its implication in the invasion of the tumor [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Un estudio realizado por investigadores del Viborg Hospital en Dinamarca, y otro realizado por Institutos de Salud Nacionales de Finlandia y la Universidad Tampere, reportan una menor prevalencia de cáncer en pacientes con sxf, atribuida una menor exposición al tabaco, alcohol y carcinógenos ocupacionales (35,36). Sin embargo, estudios recientes muestran la participación de fmrp en melanoma cutáneo y metástasis del cáncer de mama, así como una posible relación con el mesotelioma (37,38,39). Este fenómeno puede deberse a la interacción de fmrp con factores moleculares implicados en procesos neoplásicos, como, por ejemplo, con mdm2 y jnk; la reducción de la expresión del gen wnt7a en sxf también podría estar implicado (39,40,41).…”
Section: Comorbilidades Y Síndromes Asociados a Sxfunclassified
“…Sin embargo, estudios recientes muestran la participación de fmrp en melanoma cutáneo y metástasis del cáncer de mama, así como una posible relación con el mesotelioma (37,38,39). Este fenómeno puede deberse a la interacción de fmrp con factores moleculares implicados en procesos neoplásicos, como, por ejemplo, con mdm2 y jnk; la reducción de la expresión del gen wnt7a en sxf también podría estar implicado (39,40,41). No obstante, es necesario hacer más estudios para corroborar y entender mejor estos fenómenos.…”
Section: Comorbilidades Y Síndromes Asociados a Sxfunclassified
“…In previous studies, certain miRNAs were employed as new potential targets in cancer treatment in recent years (Fukumoto et al, 2015). Furthermore, recent studies demonstrated that the c-Jun N-terminal kinase (JNK) pathway plays a potential role in the physiopathology of peritoneal mesothelioma (Srivastava et al, 2015). The detection of the molecular changes in the etiopathogenesis and the invasion of mesothelioma would determine the essential goals of treatment.…”
Section: Introductionmentioning
confidence: 99%